A Domain Specific Language for Lessening the Effort Needed to Instantiate Applications Using GRENJ Framework - Durelli, Vinícius; Durelli, Rafael; Borges, Simone de Sousa; Braga, Rosana (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2010)
GRENJ is a white-box framework implemented in Java. White-box frameworks are reusable designs composed of a set of concrete and abstract classes so that the collaboration among these classes provides support for large-scale reuse of design and source code. However, instantiating applications by using this sort of framework is quite complex and demands detailed architectural knowledge. In order to lessen the amount of source code, effort, and expertise required to instantiate applications by using GRENJ framework, we have developed a domain specific language that manages all application instantiation issues systematically. This domain specific language facilitates the application instantiation process by acting as a facade over GRENJ framework as well as providing the user with a more concise, human-readable syntax than Java. In this paper, we contrast the major differences and benefits resulting from instantiating applications solely using GRENJ framework and indirectly reusing its source code by applying our domain specific language.